Analisis Kemampuan Pemecahan Masalah Siswa pada Materi Bentuk Aljabar Ditinjau dari Minat Belajar - Nurmala, Nurmala; Nurhayadi, Nurhayadi; Idris, Mustamin; Rizal, Muh. (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to describe the problem solving abilities of students at SMP Negeri 12 Palu in algebraic material in terms of learning interest. The method used in this research is a qualitative method. The results of this research show that; (1) At the stage of understanding the problem, all subjects were able to understand the problem, but subjects with moderate interest in learning did not write down their understanding. (2) In the stage of making a problem solving plan (MS), all subjects are able to make a problem solving plan. (3) The stage of implementing the problem solving plan, all subjects are able to carry out the problem solving plan (4) The stage of re-examining subjects with high learning interest (MT), and subjects with moderate learning interest (MS) re-examining their work. Meanwhile, subjects with low interest in learning (MR) did not re-examine the results of their work. The conclusion of this research is that MT subjects have high abilities in problem solving because they are able to fulfill all stages well. The MS subject is at a medium level of ability because even though he is able to complete each stage, he is not yet optimal. The MR subject is included in low ability because it is only able to complete several stages of problem solving without completing everything. Keywords: Algebra Form, Problem Solving Ability, Interest in Learning